PTCH1遺伝子のフレームシフト変異が認められた母斑基底細胞癌症候群の親子例 - 吉田, 将律; 木村, 祥一郎; 新宅, 正成; 沖永, 耕平; 吉川, 博政; 福永, 大二郎 (日本口腔外科学会雑誌, 2015)
Nevoid basal cell carcinoma syndrome (NBCCS) is a condition characterized by findings such as a keratocystic odontogenic tumor (KCOT), basal cell carcinoma, and small pits on the palms or the soles of the feet. The responsible gene is PTCH1. In this paper, we report on a parent and child with NBCCS in whom we resected the KCOT and confirmed a PTCH1 genetic mutation. Case 1 developed in a 14-year-old boy, and case 2 was in a 32-year-old woman, the mother of the boy of case 1. Both patients underwent multiple maxillary tumorectomies, and a histopathological diagnosis of KCOT was obtained. Genetic analysis confirmed the presence of a frameshift mutation in the PTCH1 gene in both the parent and the child. Even with the diagnostic criteria of Kimonis et al, a diagnosis of NBCCS was reached. Many similar cases of NBCCS are encountered in dentistry and oral and maxillofacial surgery, and the dentist is considered to play an important role in diagnosis, treatment, and explanation of the condition. Moreover, because some symptoms emerge with advancing age, PTCH1 genetic analysis should be proactively performed to achieve an early diagnosis.